You multiply 0.6 by 5x and 10 and you get 3x+6=-24. you then subtract 6 from both sides of the equation and you get 3x=-30. after that you divide both sides by 3 and you get x=-10. so the answer is B!
Answer:
x = 0
Step-by-step explanation:
3(x - 1) = 2x - 3 + 3x
3x - 3 = 2x - 3 + 3x
0 - 3 = 2x - 3
0 = 2x
2x = 0
x = 0 ÷ 2
<u>x</u><u> </u><u>=</u><u> </u><u>0</u>
Area = Length x Width
63 = 9 x width
Width= 63 ÷ 9 = 7 feet
Answer: 7 feet
Answer:
X=7
Y=9
Step-by-step explanation:
.y=x+2
y = 2x - 5
Use equivalents y=y so you get:
X+2=2x-5
X-2x=-5-2
-x=-7
X=7
Y=x+2=7+2=9
Answer:
Step-by-step explanation:
I assume this is a repeating decimal where the sequence continues infinitely.
Let x=.252525... then
100x-x=25.25...-0.25...
99x=25
x=25/99